Correlating magnetic resonance imaging characteristics with motor outcome in cerebral palsy children with white matter injury - Narkhede, Nilima Ananda; Save, Sushma (Nepal Journal of Neuroscience, 2023)
Introduction: Cerebral palsy (CP) is the term used to describe individuals with a movement disorder resulting from non-progressive disturbance to the developing brain. The diagnosis of CP is based on the presence of a motor deficit, and they manifest with reduced motor capacity. The most widely utilized classification system for the severity of motor limitations is the gross motor function classification system (GMFCS).Material and Methods: We tried to describe the white matter injury on Magnetic Resonance Imaging (MRI) in children with cerebral palsy irrespective of clinical subtype. We also studied if there was association between white matter injury on MRI in children with cerebral palsy and motor outcomes-gross motor function classification system Expanded and Revised(GMFCS E &R). It was an observational, Cross sectional Descriptive study with analytical wing aged between 6 months to 12 years of age carried out for 8 months. Children diagnosed to have cerebral palsy on history and clinical examination were enrolled in the study.Results: A total of 50 children diagnosed with cerebral palsy were enrolled in our study. Majority of the study sample were